The Impact of the COVID-19 Pandemic on the Number of Blood Donors in the Blood Transfusion Unit of the Indonesian Red Cross of Banda Aceh City - Akbar, Teuku Ilhami Surya; Sayuti, Muhammad; Ikhsan, Maulana (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: The implementation of COVID-19 protocols by staying away from crowded places has a negative impact on the world of health, especially blood services. The decrease in the number of blood donors affected many patients who may have died or suffered as a result of blood delivery to the hospital not being reached. This study looked at how much influence the COVID-19 pandemic had on the number of blood donors at the Blood Transfusion Unit, Indonesian Red Cross of Banda Aceh City. This type of research is a descriptive study with a cross-sectional survey design. For the interpretation of the results using a degree of meaningfulness with a significant degree, namely ? of 5% with a note of P? (0.05) then Ho is rejected, while if P ? (0.05) then Ho is accepted. Results and Discussion. In this study, the data compared was the number of blood donors for the periods 2019 and 2020. The results showed that there was a decrease in the number of blood donors, reaching 12.7% in the 2020 period compared to the 2019 period. The Mann-Whitney test showed a P-value of 0.038 (P 0.05), which means that Ho was accepted or there was a relationship between the COVID-19 pandemic and the decrease in the number of donors at the Blood Transfusion Unit of the Indonesian Red Cross of Banda Aceh City in 2020. The decline in the number of donors occurred due to the large number of donor activities that were canceled, and many people were worried about being exposed to COVID-19 when donating blood.Keywords: Pandemic, COVID-19, Blood donation